2013
DOI: 10.4028/www.scientific.net/amm.448-453.4571
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of FDI on China's Green Innovation in Manufacturing System

Abstract: This paper, by using technology of structural equation model (SEM) of the PLS model, discussed the relationship between FDI and promoting green innovation capability of MGIS. The research finds that it has a positive effect on FDI inflows to green innovation resources of MGIS inputs, but FDI information inflows have an inhibitory effect on the manufacturing green innovation human resources. At the same time, green innovation resources of MGIS inputs also have a positive effect on the green innovation capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Although environmental regulation and the relationship between environmental regulation and foreign direct investment (FDI) have significant negative effects on the efficiency of green innovation for patent-intensive manufacturing, the inbound FDI has significant positive effects when considering the wide range of industries. Furthermore, Bi, et al [76] showed that foreign direct investment (FDI), in the form of data, has a negative influence on the human resources that are committed to green innovation in manufacturing, but that it has a positive impact on the green innovation resources of the MGIS outputs. In OECD, Zamir and Mujahid [77] indicated that FDI, green energy consumption, and green innovation technology impact selected sample countries, positively.…”
Section: Effects Of Environmental Innovationmentioning
confidence: 99%
“…Although environmental regulation and the relationship between environmental regulation and foreign direct investment (FDI) have significant negative effects on the efficiency of green innovation for patent-intensive manufacturing, the inbound FDI has significant positive effects when considering the wide range of industries. Furthermore, Bi, et al [76] showed that foreign direct investment (FDI), in the form of data, has a negative influence on the human resources that are committed to green innovation in manufacturing, but that it has a positive impact on the green innovation resources of the MGIS outputs. In OECD, Zamir and Mujahid [77] indicated that FDI, green energy consumption, and green innovation technology impact selected sample countries, positively.…”
Section: Effects Of Environmental Innovationmentioning
confidence: 99%
“…The relationship between IFDI and green innovation has been thoroughly studied in the existing literature. For instance, Bi et al [ 42 ] conducted an empirical test on the impact of IFDI inflows on the green innovation capability of China’s manufacturing green innovation system. They found that IFDI inflow has a positive effect on the input of various elements of the green innovation resources, but the IFDI information inflow has inhibited the green innovation human resources; and innovation resource input plays a full intermediary role in the process of IFDI inflow affecting the green innovation capability.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…IFDI promotes technology spillovers through the demonstration, competition, flow, and correlation effects. IFDI technology spillovers provide important support for corporate green innovation [ 42 ]. From the demonstration effect, IFDI technology spillovers not only bring new equipment, new products and new technologies to local enterprises, but also bring advanced management experience to the host country.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%